RATIFYING THE CISG: ESTABLISHING DEFAULT RULES AS LEGAL CERTAINTY FOR INTERNATIONAL SALES CONTRACT - Chandra, Edwin; Lewiandy, Lewiandy (Awang Long Law Review, 2024)
International sales contracts are agreement that govern the cross-border sales of goods. Given the complexities inherent in such transactions, the United Nations on Contract for the International Sales of Goods (CISG) serves as a preventive measure to reduce misinterpretation and legal dispute between the contracting parties. However, the CISG’s applicability as a default rule remains limited due to not being ratified by certain states. The objective of this research is to analyze how the CISG act as a default rule to fulfill the legal certainty of contracting, and analyze the foreseeing challenges of ratifying the CISG in Indonesia. The research type is normative with statutory approach. The concept of default rules offers a convenient legal framework for the international sales contract that is in the absence of law. This theoretical framework was then adopted by the CISG, which instigates the phenomenon of the sticky default rules, reduce transaction cost with a complete set of interpretation and gap-filling mechanism, and ensure the legal certainty of the contracting parties. However, the ratification of the CISG may face several challenges such as the compability of the domestic law, potential conflicts of domestic interest, and high cost of legislating. Despite these challenges, ratifying the CISG in Indonesia remains feasible and beneficial for the development of international contract law.